2000
DOI: 10.1007/pl00007261
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the pressure and diameter of the carotid artery in humans

Abstract: The purpose of this study was to examine the assumption of similarity between pressure and diameter-change waveforms in humans. We measured carotid arterial pressure and diameter change, simultaneously, in six patients with heart disease. In all patients, the carotid arterial pressure-diameter relationship could, in practice, be regarded as being linear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 2 publications
2
78
0
Order By: Relevance
“…Many studies using dogs have demonstrated that arterial pressure waveforms and diameter-change waveforms are similar [1,30]. We reported the similarity between carotid arterial pressure waveforms measured with a catheter-tipped micromanometer and carotid arterial diameter-change waveforms measured by echo tracking in humans [34]. Thus, using systolic and diastolic pressure measured with a cuff-type manometer applied to the upper arm, we calibrated the maximum and minimum values of a diameter-change waveform and used it as a surrogate for a blood pressure waveform.…”
Section: Measurements Of Pressure Waveformsmentioning
confidence: 59%
“…Many studies using dogs have demonstrated that arterial pressure waveforms and diameter-change waveforms are similar [1,30]. We reported the similarity between carotid arterial pressure waveforms measured with a catheter-tipped micromanometer and carotid arterial diameter-change waveforms measured by echo tracking in humans [34]. Thus, using systolic and diastolic pressure measured with a cuff-type manometer applied to the upper arm, we calibrated the maximum and minimum values of a diameter-change waveform and used it as a surrogate for a blood pressure waveform.…”
Section: Measurements Of Pressure Waveformsmentioning
confidence: 59%
“…92 The algorithm of automated calculation is based essentially on the assumption that the observed changes of arterial diameter are linearly correlated with changes of blood pressure. 93 It is well known, however, that changes of arterial diameter follow pressure changes with a variable hysteresis, 94 and therefore this assumption could lead to an unpredictable bias. Moreover, the clinical applicability of this approach to the assessment of ventricular-arterial coupling, although promising, still needs to be demonstrated in wide populations.…”
Section: 64mentioning
confidence: 99%
“…(i) using the linear relationship between percentage changes in instantaneous BP and diameter, shown for carotid artery pressure in [60];…”
Section: Blood Pressure Measurementmentioning
confidence: 99%